PERTUMBUHAN TUNAS LATERAL TANAMAN NILAM (Pogostemon cablin Benth) SETELAH DILAKUKAN PEMANGKASAN PUCUK PADA RUAS YANG BERBEDA - Irawati, Heny; Setiari, Nintya (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
Patchouly is one of the plants that produce essential oil, i.e. patchouly oil, which is commonlÂ  used in cosmetic industry. Increasing the biomass of patchouly plants by triggering the growth could be one way to increase the production of pathouly oil. Therefore, the purpose of this research is to study the effect of apical bud cutting towards patchouly growth, and also to understand the optimum location of cutting on the nodus. The research used Complete Random Design method with 5 repetitions. There were 3 locations of cutting (R), i.e. R0 (without cutting), R1 (cutting at the first nodus), R2 (cutting at the second nodus). The observed variables are length and amount of lateral bud, wet weight, and dried weight. The data were then analysed using ANOVA with significancy level of 95%. If there were real different, the analysis were then continued using Duncan test with significancy level of 95%. The results showed that apical bud cutting gives real effect to the variable of length and amount of lateral bud. The untreated plant has the most lateral bud shorter than the treated ones. For the variables of wet and dried weight there were not any significant differents. Generally, cutting at the first nodus (R1) of patchouli plant gives better result than any other treatments.